Analisis Pola Pertumbuhan Ekonomi Daerah Dan SektorPotensial Kabupaten Magetan Tahun 2011-2015 - Juwita, Hanung Putri (2017)
This study aimed to analyze the sector and the non-base basis, and analyze the pattern and structure of economic growth in the area of sectoral Magetan 2011-2015. In this study, the data used is secondary data, GDP at constant prices by using Location Quotient (LQ), Shift Share Esteban Marquillas, and Klassen Typology analysis. LQ analysis results indicate a sector basis during the 20112015 analysis are agriculture, forestry, and fisheries; Water Supply, Waste Management, Waste and recycling; Information and Communication; Administration, defense and compulsory social security; Educational Services; Health Services and Social Work; and other services. Based on the analysis Shift Share Esteban Marquillas, potential sectors that consistently has a competitive advantage for the analysis of 2011 to 2015 there are four sectors namely the Procurement Electricity and Gas sector, Information and Communications, the Financial Services sector and the insurance sector and Other Services. Based on the analysis Typology Klassen, who consistently been in the sector classification developed and rapidly growing sectors (Quadrant I) during the period 2011 to 2015 is the Information and Communication sector and other service sectors